A 15-Year-Old with Aphasia and Right Hemiparesis - Wadowski, Benjamin; Chadha, Tanya; Wen, Andy Y. (Journal of Pediatric Intensive Care, 2017)
Takayasu arteritis (TA) is the third most common vasculitis in childhood, peaking in the second to third decades of life but affecting patients as young as 6 months of age. It often presents with nonspecific systemic symptoms, although at late stages, it may present with cardiac, renal, or focal neurologic sequelae of vascular compromise. In this case, we describe a 15-year-old patient who presented acutely with stroke. In the absence of more classic rheumatological symptoms and significant laboratory abnormalities on initial testing, the diagnosis of TA was only reached through extensive vascular imaging following consultation with multiple subspecialty teams. This case demonstrates the need to maintain a high index of suspicion for vasculitis in pediatric patients presenting with new onset stroke in the absence of known predisposing factors. Doing so may reduce the time to diagnosis, hasten treatment, and optimize outcomes.
Keywords: aphasia; arteritis; stroke; Takayasu; vasculitis